(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the present work, we consider a class of nonlinear ideal control issues, which can be designated ideal control issues in mechanics. We manage control frameworks whose elements can be portrayed by an arrangement of Euler-Lagrange or Hamilton conditions. Utilizing the variety structure of the arrangement of the relating limit esteem issues, we decrease the underlying ideal control issue to a helper issue of multi target programming. This procedure makes it conceivable to apply some steady numerical approximations of a multi target streamlining issue to the underlying ideal control issue. For taking care of the assistant issue, we propose an implementable numerical al-algorithm